A common ground in Guerilla Marketing – State of research and further research opportunities (Junior Management Science, 2016)
Guerilla Marketing is a cloudy concept. While practitioners and scientists increasingly use it in their practice, its definition remains not straightforward. This thesis builds a common ground in Guerilla Marketing through clearing up the field. Guerilla Marketing is defined and an overall model is presented that integrates previous efforts. This model has some advantages. Most strikingly, it introduces two highly relevant mediators which include recipient’s behavior into the model.Keywords: Guerilla Marketing, Marketing science, Conceptual framework, Philosophy of science